Early Emerging Gradients in Children's Eye Movement Times Across Levels of Household Resources - Leppänen, Jukka M.; Pyykkö, Juha; Evans, Denise; Coetzee, Lezanie; Fink, Günther; Yousafzai, Aisha K.; Hamer, David H.; Parkerson, Doug; Rockers, Peter C. (WILEY, 2026)
Studies in low-resource settings suggest that multiple aspects of early childhood development are sensitive to the relative poverty of a child's environment. We examined whether direct, quantitative measures of early developing cognitive functions show a similar association with relative poverty. Eye movement latencies were recorded in children at 7, 17, and 36 months in rural South Africa (N = 374). The latency to respond to the appearance of visual objects was inversely associated with a proxy measure of the child's socioeconomic environment (household asset ownership), with longer latencies observed in children from households with less asset-based resources. This gradient was detectable at 7 months, increased between 7 and 36 months, was not explained by differences in prior exposure to screens, and generalized to the latency of eye movements towards socially cued objects (i.e., pointing gestures that directed the child's attention to a specific object). Physical growth (height-for-age) and developmental milestone scores were lower in children from households with less resources. The results were replicated in an analysis of independent data from 31-month-old children collected in Zambia (N = 270). The results provide novel evidence for early emerging gradients in behaviors that are universal and mechanistically involved in learning and skill formation.Summary Eye tracking was used to assess whether the early development of elementary visual behaviors is associated with the relative poverty of the environment in low-resource settings. Eye movement latencies to the onset of visual stimuli were longer in children from relatively poorer environments, with suggestive evidence for a steepening of this gradient over early childhood. A similar gradient across poverty levels was seen in eye movement latencies to dynamic social spatial cues (gaze and hand gestures) This study provides novel, quantitative evidence for very early-emerging gradients in behaviors that are essential for adaptive functioning and learning across all environments.